Peptidomimetics Protocols - Kazmierski, Wieslaw M.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 1999)
In Peptidomimetics Protocols, Wieslaw Kazmierski assembles a state-of-the-art collection of detailed synthetic procedures that lead to a variety of scaffolds, turn mimetics, peptide-bond replacements, and enzyme inhibitors. Topics range from syntheses of unusual amino acids, to the use of a variety of linear and heterocyclic scaffolds in place of the peptide backbone. Important chemical procedures and methods include the transient protection of charged peptides as neutral prodrugs for improved blood-brain penetration and the replacement of otherwise labile peptide bonds with heterocyclic rings, olefins and fluoroolefins, and ketomethylenes. Synthetic protocols towards the transition-state mimics and reactive "warheads," applicable in enzyme inhibitors, are also disclosed. Peptidomimetics Protocols is the first book devoted to the practical synthetic preparation of peptide mimetics. Written by both academic and industrial synthetic organic and medicinal chemists, this book provides highly practical synthetic procedures for the generation of key peptide mimetics, and so immediately becomes a must-have desk reference and guide for all medicinal and pharmaceutical chemists engaged in the discovery and development of pharmaceuticals today.
Synthesis and Use of Pseudopeptides Derived from 1,2,4-Oxadiazole-, 1,3,4-Oxadiazole-, and 1,2,4-Triazole-based Dipeptidomimetics -- Synthesis of Aminobenzoic Acid-Based Nonpeptide Templates: Applications in Peptidomimetic Drug Discovery -- Synthesis of an Esterase-Sensitive Cyclic Prodrug of a Model Hexapeptide Having Enhanced Membrane Permeability and Enzymatic Stability Using an Acyloxyalkoxy Promoiety -- Synthesis of an Esterase-Sensitive Cyclic Prodrug of a Model Hexapeptide Having Enhanced Membrane Permeability and Enzymatic Stability Using a 3-(2?-Hydroxy-4?,6?-Dimethylphenyl)-3,3-Dimethyl Propionic Acid Promoiety -- Synthesis of Coumarin-Based, Esterase-Sensitive Cyclic Prodrugs of Opioid Peptides with Enhanced Membrane Permeability and Enzymatic Stability -- Azatides as Peptidomimetics: Solution and Liquid Phase Syntheses -- Synthesis of Cbz-Protected Ketomethylene Dipeptide Isosteres -- (E)-Alkene Peptide Bond Isosteres by Cuprate Opening of Vinyl Aziridines -- Syntheses of Norstatine, Its Analogs, and Dipeptide Isosteres by Means of ?-Lactam Synthon Method -- Synthesis of a Versatile Peptidomimetic Scaffold -- An Asymmetric Synthesis Protocol to Prepare Topographically Constrained ?-Substituted Aromatic Amino Acids -- Synthesis of Oligopeptides Containing an Oxirane Ring in the Place of a Peptidic Bond -- Synthesis of Protected Lactam-Bridged Dipeptides -- Synthesis of Peptidomimics Through Sugar-Based Scaffolds -- The Synthesis of Bicyclic Piperazinone and Related Derivatives -- Synthesis of Dipeptides with ?[CH20] Amide Bond Mimetics -- SNAr-Based Cycloetherification Methodology: Application in the Synthesis of Heterodectic Macrocyclic Peptides with Endo Aryl-Aryl and Aryl-Alkyl Ether Bonds -- Cyclic Aromatic Amino Acids with Constrained ?1 and ?2 Dihedral Angles -- Asymmetric Syntheses of Unnatural Amino Acids and Hydroxyethylene Peptide Isosteres -- Fluoroolefin Isosteres -- Synthesis of 3-Amino-l-CarboxymethyI-Benzodiazepine (BZA) Peptidomimetics -- A Conformationally Restricted ?-Strand HIV Protease Inhibitor -- Synthesis of Cyclopropane-Containing Leu-Enkephalin Analogs -- The 1,5-Disubstituted Tetrazole Ring as a cis-Amide Bond Surrogate -- Synthesis of (2R, 3R, 4R, 5S)-5-tert-Butyloxycarbonylamino-3,4-Dihydroxy-2-1sopropyl-3,4-O,O-Isopropylidene-6-CyctohexyI-Hexanoic Acid -- Synthesis of (2S, 4S, 5S)-5-(t-Butoxycarbonylamino)-4-(t-Butyldimethylsilyloxy)-2-Isopropyl-7-Methyl Octanoic Acid -- Synthesis of ?-Vinyl Amino Acids -- A Novel Synthetic Protocol for the Preparation of Enantiopure 3-, 4-, and 5-Substituted Prolines -- Synthesis of Aminobenzoic Acid-Based Nonpeptide Templates -- Aminimides as Peptidomimetics.
Keywords: Medicinal chemistry; Medicinal Chemistry